2015
DOI: 10.2217/fmb.15.35
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Locus Variable Number Tandem Repeat Analysis is Superior to Spa Typing and Sufficient to Characterize MRSA for Surveillance Purposes

Abstract: MLVA is superior to spa typing and will suffice to characterize MRSA isolates for surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…SCC mec typing, which classifies SCC mec elements on the basis of their structural differences, is applied in several epidemiological studies of MRSA strains (Turlej et al, 2011). Molecular characterization of S .aureus is vital for the rapid identification of prevalent strains and will contribute to the control and prevention of S. aureus spread around healthcare settings if results are provided in real time (Siegel et al, 2007; Bosch et al, 2015; O'Hara et al, 2016). Phage typing was originally used for the formal typing of S. aureus isolates, but it was gradually replaced by pulsed-field gel electrophoresis (PFGE), the most recent gold standard method for the typing of S. aureus isolates (Bannerman et al, 1995; Murchan et al, 2003; Bosch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCC mec typing, which classifies SCC mec elements on the basis of their structural differences, is applied in several epidemiological studies of MRSA strains (Turlej et al, 2011). Molecular characterization of S .aureus is vital for the rapid identification of prevalent strains and will contribute to the control and prevention of S. aureus spread around healthcare settings if results are provided in real time (Siegel et al, 2007; Bosch et al, 2015; O'Hara et al, 2016). Phage typing was originally used for the formal typing of S. aureus isolates, but it was gradually replaced by pulsed-field gel electrophoresis (PFGE), the most recent gold standard method for the typing of S. aureus isolates (Bannerman et al, 1995; Murchan et al, 2003; Bosch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular characterization of S .aureus is vital for the rapid identification of prevalent strains and will contribute to the control and prevention of S. aureus spread around healthcare settings if results are provided in real time (Siegel et al, 2007; Bosch et al, 2015; O'Hara et al, 2016). Phage typing was originally used for the formal typing of S. aureus isolates, but it was gradually replaced by pulsed-field gel electrophoresis (PFGE), the most recent gold standard method for the typing of S. aureus isolates (Bannerman et al, 1995; Murchan et al, 2003; Bosch et al, 2015). However, due to its laborious character and difficulties in exchanging data between laboratories, and the requirement for inter-laboratory standardization, PFGE was replaced by multi-locus sequence typing (MLST) and staphylococcal protein A ( spa ) typing (Harmsen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, non-typeable (NT) isolates are increasingly found in the Dutch MRSA surveillance as well as globally. Thus, to overcome the issue of NT strains, other typing method should be concurrently used to be a supportive method [60]. Malachowa et al [61] found that spa typing was more approximate to MLST approach upon comparing four genotyping methods (PFGE, MLST, MLVA and spa typing) in 59 S. aureus strains.…”
Section: Staphylococcal Protein a (Spa) Typingmentioning
confidence: 99%
“…Similar clonal spread of MRSA (methicillin-resistant Staphylococcus aureus) and MSSA (methicillin-susceptible Staphylococcus aureus) is becoming pandemic in many several communities in Africa, mostly Nigeria where animal husbandry, behavioural responses and declined demographic factors enhance continuous dissemination of staphylococcal infection with high degree of antibiotic resistance [9]. The misuse and unregulated prescription of penicillin derivatives in high and uncontrollable proportion for treating several extra-intestinal infections such as abscess, ear infections, subcutaneous tissue inflammation, nasal discharges particularly in children and postsurgical wound culminated in a high rate of resistance and continuous development of methicillin-resistance strains [10,11].…”
Section: Introductionmentioning
confidence: 99%